PENGARUH POLA ASUH ORANG TUA DAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR AL-QUR’AN SANTRI MADRASAH DINIYAH THORIQUL HUDA NAMPAN SUKOREJO PONOROGO TAHUN PELAJARAN 2021/2022 - Isni Khoirun Nimah; Muhammad Heriyudanta (TA'LIM : Jurnal Studi Pendidikan Islam, 2022)
This study examines the description of the motivation to learn the Qur'an and whether or not the influence of parenting patterns of parents and peers on the motivation to learn the Qur'an of the students of Madrasah Diniyah Thoriqul Huda Nampan Sukorejo Ponorogo in the 2021/2022 academic year. This study aims to determine the effect of parenting patterns of parents and peers on the motivation to learn the Qur'an of the students of Madrasah Diniyah Thoriqul Huda Nampan Sukorejo Ponorogo in the 2021/2022 academic year. This study examines a number of 50 students. Data collection techniques using observation, documentation, and questionnaires. Questionnaire technique is used to answer written statements to respondents. Data analysis technique with simple linear regression analysis. The conclusions of this study are (1) parenting styles have a significant effect on students' motivation to learn the Qur'an at Madrasah Diniyah Thoriqul Huda, in the medium category with a percentage of 19.3%. (2) Peers have a significant effect on the motivation to learn the Qur'an of Madrasah Diniyah Santri Thoriqul Huda in the medium category with a percentage of 24%. (3) Parenting patterns of parents and peers have a significant effect on learning motivation of the Qur'anic students of Madrasah Diniyah Thoriqul Huda, in the medium category with a percentage of 34.1%.